PENGARUH PIJAT OKSITOSIN PADA IBU MENYUSUI TERHADAP KELANCARAN ASI DI PMB PANCORAN MAS TAHUN 2022 - Wahyuni, Dwi Reza (Politeknik Tiara Bunda, 2022)
Background: Breast milk does not come out due to the condition of not producing breast milk or at least producing breast milk caused by the oxytocin hormone that does not work because of the lack of stimulation of the baby's sucking which activates the work of the oxytocin hormone. When a nursing mother experiences stress or discomfort, there will be an inhibition of the let down reflex so that it will reduce milk production. Objectives: To determine the effect of Oxytocin Massage on Breastfeeding Mothers on Breastfeeding Smoothness at PMB A. Hermayani Bekasi in 2022. Methods: This research is a one group pre test post test. The population in this study were all breastfeeding mothers who experienced irregular breastfeeding at PMB A Hermayani Bekasi a total of 30 mothers. Results: the effect of cytosine massage before being given an intervention is lower I < 2 is the minimum value after being given an intervention which increases by a difference of I. The median value after being given the intervention has increased by 1> 3 with a difference of 2 While the maximum after being given the intervention has increased: I> 4 with a difference of 3. means there is a significant increase with a p-value of 0.000 meaning H0 is rejected and H1 is accepted, which means that there is an effect of oxytocin massage on breastfeeding mothers on the smooth production of breast milk at PMB A. Hermayani in 2022. Conclusion: The smoothness of breast milk in breastfeeding mothers before oxytocin massage was carried out at PMB A. Hermayani Bekasi In 2022, most of the milk production was not smooth. The smoothness of breast milk in nursing mothers after oxytocin massage was carried out at PMB A. Hermayani Bekasi in 2022, most of the milk output was smooth. There was an effect of oxytocin massage on smooth milk in PMB A. Hermayani Bekasi in 2022